2015
DOI: 10.1111/aeq.12119
|View full text |Cite
|
Sign up to set email alerts
|

“Denial or Faith?” Therapy Versus Messianism in Preparing for the Evacuation of Israeli Settlements

Abstract: This article offers an ethnographic account of the professional activities of mental health practitioners, employed by the state's religious education system. I analyze various models implemented by practitioners for the purposes of preparing pupils for the state-mandated evacuation of Jewish settlers from Gaza and the West Bank. By focusing on the interaction between psychological and religious-national cultural frameworks I show how practitioners imbue familiar professional concepts with new meanings and cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…When approaching this study, I assumed that the therapists who identified with religious Zionism would stress the role of the traumatic event as the determining factor in the patient's suffering. This assumption was grounded on a moral grammar of traumatic narrative which implies the moral innocence of victims (Brunner, 2002; Young, 1995) and the perception of the political and moral subjectivity of the ideologically oriented psychotherapists (McKenny, 2007; Plotkin Amrami, 2016). Thus, I anticipated that the patient's symptoms would be explained in the described clinical setting as a direct result of the Disengagement experience rather than a feature of her personal qualities or her parents’ functioning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When approaching this study, I assumed that the therapists who identified with religious Zionism would stress the role of the traumatic event as the determining factor in the patient's suffering. This assumption was grounded on a moral grammar of traumatic narrative which implies the moral innocence of victims (Brunner, 2002; Young, 1995) and the perception of the political and moral subjectivity of the ideologically oriented psychotherapists (McKenny, 2007; Plotkin Amrami, 2016). Thus, I anticipated that the patient's symptoms would be explained in the described clinical setting as a direct result of the Disengagement experience rather than a feature of her personal qualities or her parents’ functioning.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, I examine a group of psychotherapists who provided mental health services for the displaced settlers in the aftermath of the events. Previous ethnographic studies on professional practices implemented in the Disengagement context have shown how this political event led to a clash between the therapeutic rationale of preparing for a traumatic event, on the one hand, and the ideological impulse to resist the political decision, on the other (Plotkin Amrami, 2015, 2016). At the same time, these studies demonstrated how the integration of therapeutic assumptions with a messianic ideology by ideological-religious therapists produced new meanings for familiar concepts and new hybrid models for intervention.…”
Section: Research Setting and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, many evacuees eventually accepted the assistance offered by the Center. As I have written elsewhere (Plotkin‐Amrami ; ), this may be related to the interventional models developed by Mahout. These fused Religious Zionist thought and the therapeutic ethos, and linked at once the contradictory imperatives for resistance to and preparation for evacuation.…”
Section: Methods and Contextmentioning
confidence: 99%